Degradasi Zat Warna Malachite Green Menggunakan Katalis TiO2 dengan Metode Fotolisis - Miftahurrahmi, Miftahurrahmi; Sanjaya, Hary; Oktavia, Budhi; Nizar, Umar Kalmar (Departemen Kimia FMIPA UNP, 2023)
The research that has been done on the photolysis of the degradation of Malachite Green using TiO2 catalyst aims to determine the effect of the percentage degradation of the Malachite Green solution. The results of UV-Vis spectrophotometer measurements obtained a wavelength of 617nm. The results showed that the highest percentage of degradation was 99.05% at 210 minutes using TiO2 catalyst, while 65.45% with TiO2 catalyst mass of 0.25 grams. This study shows that the hydroxyl radical (∙OH) is the main control in degrading Malachite Green.